Two Unusual Aspects of Posterior Reversible Encephalopathy Syndrome Mimicking Primary and Secondary Brain Tumor Lesions - Mazamaesso Tchaou; Nicoleta Modruz; Lama K. Agoda-Koussema; Anthony Michelot; Samer Naffa; Véronique Jeudy; Raymond Kaczmarek (Case Reports in Radiology)
The posterior reversible encephalopathy syndrome (PRES) is a rare clinical-radiological entity well described with typical clinical and radiological manifestations. Atypical presentation, especially in imaging, exists. The authors report here two cases of posterior reversible encephalopathy in which imaging aspects were atypical, mimicking, in the first case, hemorrhagic cerebral metastasis of cholangiocarcinoma and, in the second case, a brain tumor. The diagnosis has been retrospectively rectified due to clinical and radiological outcome.